1989
DOI: 10.1002/1097-0142(19900501)63:9<1721::aid-cncr2820630913>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar soft part sarcoma. An ultrastructural and lmmunocytochemical investigation of its histogenesis

Abstract: Fourteen alveolar soft part sarcomas were studied using electron microscopic analysis and a battery of immunocytochemical procedures in order to critically assess the extent to which these methods could explain the histogenesis of the tumor. All the tumors were stained with antibodies against keratin, vimentin, S‐100 protein, Leu‐7, neuron‐specific enolase, desmin, muscle‐specific actin, myoglobin, smooth muscle myosin, and fast and slow myosins. Eight tumors stained for vimentin, eight for desmin, eight for n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…The cytoplasmic endoplasmic reticulum is as a rule sparse, mitochondria are numerous, and Golgi apparatus is greatly developed [43]. The latter is associated with crystalloids or precrystallized electron-dense granules mentioned above both of which are membranebound [31,43,47].…”
Section: Ultrastructurementioning
confidence: 97%
See 3 more Smart Citations
“…The cytoplasmic endoplasmic reticulum is as a rule sparse, mitochondria are numerous, and Golgi apparatus is greatly developed [43]. The latter is associated with crystalloids or precrystallized electron-dense granules mentioned above both of which are membranebound [31,43,47].…”
Section: Ultrastructurementioning
confidence: 97%
“…Mitoses are few and necrosis rare. Other possible aspects are nuclear pseudoinclusions, cystic or myxoid changes, stromal sclerosis, calcification, and chronic inflammatory infiltrate [2,13,[42][43][44][45][46][47][48][49][50]. Rarely, some tumors display a high mitotic rate, polymorphism, spindling, and xanthomatous changes [9].…”
Section: Light Microscopymentioning
confidence: 99%
See 2 more Smart Citations
“…The popular use of immunohistochemistry beginning in the late 1970s allowed us for the first time to turn attention to these crystals by applying a host of antibodies to these tumors with variable and sometimes conflicting results. [5][6][7][8][9][10][11][12][13] The most celebrated of all theories regarding the alveolar soft part sarcoma was that it represented an unusual myogenous tumor closely related to a rhabdo-myosarcoma. 9,10 Numerous immunohistochemical studies, however, demonstrated muscle markers in less than half of ASPS.…”
mentioning
confidence: 99%